Introdução à programação de computadores por meio de uma tarefa de modelagem matemática na educação matemática - Carvalho, Felipe José Rezende de (2018)
Mathematical Modeling is a trend of Mathematics Education that values, among other things, the exploratory work by the students on themes linked to daily life.It creates the possibility of a an interdisciplinary work together with other tendencies, allowing the construction of knowledge in a dynamic way. Our interest is in the area of inquiry that concerns the association of Mathematical Modeling and Digital Technologies of Information and Communication, specifically regarding the possibilities and challenges of allying computer programming to a Mathematical Modeling task. Moved by this interest, we establish the question: What is revealed of a task of Mathematical Modeling, in the environment of computer programming, developed by students of Basic Education? We seek to understand what is shown when we develop a Mathematical Modeling task allied to computer programming and what the possibilities and the challenges are which emerge from this association. This question guided all research, conducted by a qualitative approach according to a phenomenological view. In order to account for our questioning, we constructed a task of Mathematical Modeling that was developed by students of Basic Education of a public school in the interior of the state of Minas Gerais, through programming in blocks, using Scratch software. The development of this task was recorded by filming videos that were watched several times in such a way that, in the light of our research question, we could highlight relevant passages that converged to our question, and, from them, build our units of meaning. After the construction of these units, from repeated readings, we established convergences, which culminated in four categories, namely: C1: On the debates, discussions and talks between students and between students and teachers in the development of the task; C2: On the actions of the students in the context of the Modeling task; C3: On relationships with school mathematics that emerged in the development of the Modeling task; C4: On the ways students viewed the project. These categories, interpreted hermeneutically, allowed us to observe, among other things, that the task of Modeling guided the development of computational thinking through a computer programming activity, strengthening the discussions and reflections on the context involved by the task, opening space to learn-with-another, in a dialogic and dynamic environment built by the synergy of Modeling with computer programming.